Association between infection and nutritional status among infants in a cohort study of vitamin A in western Kenya - Grant, F.; Wanjala, R.; Low, Jan W.; Levin, C.; Cole, Donald C.; Okuku, H.S.; Ackatia-Armah, R.; Girard, Amy W. (Frontiers Media, 2022)
BackgroundInfection is associated with impaired nutritional status, especially for infants younger than 5 years. ObjectivesWe assessed the impact of infection indicated by both acute phase proteins (APP), C-reactive protein (CRP), and alpha-1-acid-glycoprotein (AGP), and as reported by maternal recall on the nutritional status of infants. Materials and methodsA total of 505 pregnant women were enrolled in a nested longitudinal cohort study of vitamin A (VA). Data from 385 children are reported here. The incidence and severity of respiratory infection and diarrhea (previous 14 days) were assessed by maternal recall; infant/child feeding practices were collected. Infant weight, recumbent length, and heel-prick capillary blood were taken at 9 months postpartum. Indicators of the VA status [retinol binding protein (RBP)], iron status (Hb, ferritin), and subclinical inflammation APP, CRP (>5 mg/L), and AGP (>1 g/L) were determined. Impacts of infection on the infant nutritional status were estimated using logistic regression models. ResultsInfection prevalence, based on elevated CRP and AGP levels, was 36.7%. For diarrhea reported symptoms, 42.4% of infants at 9 months had no indication of infection as indicated by CRP and AGP; for acute respiratory reported symptoms, 42.6% had no indication of infection. There was a significant positive association with infection among VA-deficient (RBP < 0.83 mu mol/L) infants based on maternal reported symptoms but not with iron deficiency (ferritin < 12 mu g/L). The odds of having infection, based on increased CRP and AGP, in underweight infants was 3.7 times higher (OR: 3.7; 95% CI: 2.3, 4.5; P = 0.019). Infants with iron deficiency were less likely (OR: 0.40; 95% CI: 0.1, 0.7; P = 0.001) to have infection based on CRP and AGP, while infants with VA deficiency were five times more likely (OR: 5.06; 95% CI: 3.2, 7.1; P = 0.0001) to have infection. ConclusionAcute phase proteins are more useful in defining infection in a population than reported symptoms of illness. Not controlling for inflammation in a population while assessing the nutritional status might result in inaccurate prevalence estimation.